PLATFORM PEDAGOGIES: LEARNING, AUTHORISING AND VALIDATING TRUST IN EDUCATION - Sefton-Green, Julian; Zacher Pandya, Jessica; Hendry, Natalie; Pangrazio, Luci (AoIR Selected Papers of Internet Research, 2019)
This panel investigates the pedagogic dimension of digital platforms thus drawing on older theoretical traditions that use pedagogy as a way of describing and explaining the relationships between individual and society, agency and structure (paper 1). We want to explore what it means to conceive of the relationship between people and their platforms as a pedagogic relationship; and how such conceptualisations might advance study of platforms in general (paper 4). Additionally, using the term pedagogy in its more specifically educational sense the panel explores the relationship between learning, schooling and education systems across emerging platforms (papers 2 regarding 8th grade teachers in the US using apps, and paper 3 regarding Australian universities’ learning management systems). Platforms, we argue, standardise and seek to offer a relationship of trust over time with their “citizens”. Platforms working with families, schools or in higher education feed off the authority and trust that pertains between citizens and these institutions. However, the platformisation of education (van Dijck, Poell & de Waal, 2018) may contain other kinds of risks for students and their families, thereby introducing the need for new forms of validation. By thinking about activities in and across a series of platforms in terms of pedagogic relationships, where trust is placed in authority, the panel will explore the mechanisms by which digital interactions take forms of social trust and yet expose people to forms of dataveillance beyond ways that any membership or participation suggests in its initial contract.